Klasifikasi Kecanduan Bermain Game online Pada Remaja Menggunakan Metode Naïve Bayes Classifier Berbasis Website - Suci Pania, Tika; Hidayati, Rahmi; Kasliono, Kasliono (STMIK Budi Darma, 2024)
The use of electronic devices such as cellphones, laptops, and others is often found for various reasons, including playing online games. Online games are very popular because they can relieve stress and can be played by various ages, one of which is teenagers aged 10-19 years. However, online games can be detrimental to teenagers. If a teenager plays online games for a long time, that teenager will become dependent on online games. This research creates a system that can help teenagers find out their level of addiction to online games, so that teenagers can overcome their addiction problems. This system classifies addiction to playing online games in teenagers with mild, moderate and severe levels using the Naïve Bayes Classifier method. This system can help teenagers control themselves when playing online games. In determining the level of online game addiction, 5 attributes are used, namely age, gender, place of play, type of game, and length of play. Testing with 150 data and tested with nine comparisons of training data and test data, namely 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, 80:20, and 90: 10. Testing is carried out using a confusion matrix to produce accuracy, precision, recall and error rate values. The highest accuracy value is found in comparing training data and test data of 40:60. Accuracy results were 93%, precision was 90%, recall was 89%, and error rate was 6.67%.